The Effect Of Workload And Work Compesation On Employee Satisfaction At TPST Cirejag, Jatisari District Karawang Regenc - Amalia Puspitasari; Budi Rismayadi; Wike Pertiwi (Economics and Digital Business Review, 2026)
The research sample consisted of 36 employees at the Cirejag Integrated Waste Treatment Facility in Jatisari Subdistrict, Karawang Regency, selected using a saturation sampling technique to cover the entire population. A strictly verifiable quantitative approach was applied. Primary data were collected via a questionnaire using a Likert scale, while secondary data were obtained from field observations, brief interviews, and a comprehensive literature review. Data analysis was conducted using multiple linear regression with SPSS version 26 software, yielding the following findings. Partially, the impact of workload on employee job satisfaction was negative but not statistically significant. On the other hand, compensation has a significant positive influence. When considered simultaneously, workload and compensation together significantly influence job satisfaction, with a coefficient of determination reaching 50 percent, indicating that half of the variation in job satisfaction can be explained by these two variables, while the remainder depends on external factors. From these specific findings, it can be generally concluded that human resource management in the waste management sector, such as at the Cirejag Integrated Waste Treatment Facility, must prioritize a balance between workload and proportional compensation to sustainably improve public service standards